FAMILY KEROPLATIDAE - Falaschi, Rafaela Lopes (Zootaxa, 2016)
Currently, 86 genera are ascribed to the Keroplatidae, with about 950 known species. The family includes three subfamilies: Arachnocampinae, Macrocerinae, and Keroplatinae. Both Macrocerinae and Keroplatinae are found in Colombia, with five described species distributed in four genera. The available information about Colombian keroplatids is compiled, with new records for five genera.